3-Azaspiro[5, 5]undecan-2, 4-dioxo-3-yl diphenyl phosphate (ASUD-diphenyl phosphate), a new reagent for the synthesis of the N-protected amino acid-ASUD ester. Issue 11 (1st July 2016) - Rao, B. Leelamaheswara; Nowshuddin, Shaik; Jha, Anjali; Divi, Murali K.; Rao, M.N.A.
Graphical abstract: Abstract: A new reagent, 3-azaspiro[5, 5]undecan-2, 4-dioxo-3-yl diphenyl phosphate (ASUD-diphenyl phosphate) is described for the synthesis of N -protected amino acid-ASUD esters which are active esters useful in the synthesis of peptides. This compound was synthesized by reacting N -hydroxy-3-azaspiro[5, 5]undecane-2, 4-dione (HO-ASUD) with diphenyl chlorophosphate in the presence of a base at room temperature and was obtained in high yields. The ASUD-diphenyl phosphate reagent reacts with N -protected amino acids under mild conditions to give the corresponding ASUD active esters, while preserving the enantiomeric purity of the amino acid. The new reagent is a stable crystalline compound and eliminates the need for DCC, a potent skin allergen, used previously for the synthesis of N -protected amino acid-ASUD ester. Abstract : Methyl ( tert -butoxycarbonyl)-l -phenylalanyl-l -phenylalaninate: C24 H30 N2 O5 [ α ]D 25  = −13.8 ( c 1, CH3 OH) Source of chirality: the precursor Absolute configuration: L Abstract : tert -Butyl ( R )-(1-(benzylamino)-3-methoxy-1-oxopropan-2-yl)carbamate: C16 H24 N2 O4 [ α ]D 25  = −20.8 ( c 0.9, CHCl3 ) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( R )-2-Acetamido- N -benzyl-3-methoxypropanamide: C13 H18 N2 O3 [ α ]D 25  = +16.0 (c 1, CH3 OH) Source of chirality: the precursor Absolute configuration: ( R )